2019
DOI: 10.2147/cmar.s189627
|View full text |Cite
|
Sign up to set email alerts
|

<p>A systematic review of international guidelines and recommendations for the genetic screening, diagnosis, genetic counseling, and treatment of <em>BRCA</em>-mutated breast cancer</p>

Abstract: PurposeTo conduct a systematic review of international guidelines on screening and management of patients with BRCA-mutated breast cancer (BC).MethodsMajor electronic databases (MEDLINE and Embase; N=8) and gray literature sources were searched (January 2007 to February 2018). Latest guideline recommendations on genetic screening, counseling, and BC treatment of BRCA mutation carriers were summarized. Guidelines specific to germline BRCA (gBRCA) mutation were captured where available.ResultsA total of 3,775 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
88
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(90 citation statements)
references
References 49 publications
0
88
0
2
Order By: Relevance
“…Tumor and germline genetic testing is variably performed in patients affected by breast (92) and ovarian carcinomas (93). It has been shown that triaging women for genetic testing based on family history alone will miss up to 30% of affected individuals (94).…”
Section: Genetic Testingmentioning
confidence: 99%
“…Tumor and germline genetic testing is variably performed in patients affected by breast (92) and ovarian carcinomas (93). It has been shown that triaging women for genetic testing based on family history alone will miss up to 30% of affected individuals (94).…”
Section: Genetic Testingmentioning
confidence: 99%
“…It has recently been observed that the prevalence of BRCA pathogenic variant carriers is higher than previously estimated (38) and that current clinical guidelines fail to identify an important proportion of patients carrying the pathogenic variants (18,19,21,39). Consequently, recent updates of the referral guidelines recommend referral of women with less remarkable family history of cancer (8). Studies that examined older versions of NCCN guidelines for HBOC referral of women from the general population identi ed more women with each update (17,22,23).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is less common to refer unaffected women to genetic counseling for gynecological cancers, even when they harbor a family history of cancer and genetic counseling and testing would provide important information for their cancer risk evaluation (7). Identi cation of a pathogenic variant in asymptomatic women presents an opportunity to tailor appropriate monitoring and surveillance for breast and other cancers, in addition to offering prophylactic, risk-reducing interventions (8). The process of genetic testing begins with a referral from a general practitioner or oncologist to a genetic counselor; therefore, patients strongly rely on physician identi cation and referral for genetic counseling.…”
Section: Introductionmentioning
confidence: 99%
“…All international guidelines highlighted the importance to identify gBRCA1/2 mutations carriers by performing genetic counseling as early as possible during the course of disease in patients at risk of inherited disease, given the implication in decision-making process in terms of the type of surgery, radiotherapy, and systemic treatment either in neo-(adjuvant) and advanced settings [33].…”
Section: Brca1/2 Mutationsmentioning
confidence: 99%